RECOVERY OF JAPAN'S TRADE BALANCE SURPLUS AS THE ENGINE OF THE ECONOMY GROWTH - D. Shevchenko (Publishing House of the State University of Management, 2017)
The article analyzes the trade balance of Japan, exports and imports over the past two years. The general results of the first and second quarters of 2017 have been summed up, which make it possible to talk about the prospects for the growth of the Japanese economy and, most important, highlight the changes in the export structure that are associated with both the restoration of the automotive industry's traffic flow and the dynamics of semiconductor exports, and subsequent consumer demand dynamics implementation of the socio-economic development strategy set by the Government of Japan.